The practice of the Commercial Court - Stanuell, Charles A. (Statistical and Social Inquiry Society of Ireland, 1906)
I must preface my remarks upon this subject by stating that the Commercial Court to which I allude has no existence in Ireland, and therefore I am at a disadvantage in dealing with a system of judicial procedure with which I have no personal experience. I am somewhat in the same position in which an English lawyer would be if he were to attempt to address an English audience on the practice of the Estate Commissioners. At the same time, it may serve a useful purpose to show how far the great commercial and mercantile classes have been able to bend the rigidity of judicial procedure, and for this purpose I propose to give a brief account of what is called in England the "Commercial Court" though really it is a separate list of a certain class of Common Law or King's Bench Actions. In my account I propose to rely upon Mr. Mathew's Practice of the Commercial Court, supplemented by information obtained from professional brethren in England.
Read November 24th, 1905
Keywords: Commercial law; English legal system; Commercial Court; 314.15